2015
DOI: 10.7717/peerj.810
|View full text |Cite
|
Sign up to set email alerts
|

ProspectingRussula senecis: a delicacy among the tribes of West Bengal

Abstract: Russula senecis, a worldwide distributed mushroom, is exclusively popular among the tribal communities of West Bengal for food purposes. The present study focuses on its reliable taxonomic identification through macro- and micro-morphological features, DNA barcoding, confirmation of its systematic placement by phylogenetic analyses, myco-chemicals and functional activities. For the first time, the complete Internal Transcribed Spacer region of R. senecis has been sequenced and its taxonomic position within sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 34 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…One such less explored taxon is Russula senecis that has recently been documented as a new member to macrofungal flora of West Bengal, India. Interestingly, the specimen also emerged as a seasonal health promoting food among local indigenous people indicating safety for human consumption ( Khatua et al, 2015 ). Recently, medicinal activity of polysaccharide from the mushroom has been established in our previous study, although 10% NaOH solution was used as an extractant solvent ( Khatua and Acharya, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…One such less explored taxon is Russula senecis that has recently been documented as a new member to macrofungal flora of West Bengal, India. Interestingly, the specimen also emerged as a seasonal health promoting food among local indigenous people indicating safety for human consumption ( Khatua et al, 2015 ). Recently, medicinal activity of polysaccharide from the mushroom has been established in our previous study, although 10% NaOH solution was used as an extractant solvent ( Khatua and Acharya, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…3). Several authors have reported the hydroxyl radical scavenging effect of various mushrooms (Oyetayo, 2009;Khatua et al, 2015). Hydroxyl radical is an extremely reactive oxygen species that can propagate a chain reaction, wreaking havoc on many biological molecules such as DNA and lipids (Uttara et al, 2009;Kumar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The mobile phase consisted of eluent A (acetonitrile) and eluent B (aqueous phosphoric acid solution, 0.1% v/v). A gradient program was used for elution: 0-2 min, 5% A; 2-5 min, 15% A; 5-10 min, 40% A; 10-15 min, 60% A; 15-18 min, 90% A (Khatua et al 2015). Gallic acid, p-coumaric acid, myricetin, caffeic acid, vanillic acid, ferulic acid, quercetin, cinnamic acid and pyrogallol (M.P.…”
Section: Quantification Of Phenolic Compounds By Hplcmentioning
confidence: 99%
“…Biomedicals. USA) were used as standards according to Khatua et al (2015). The DAAD detection was conducted at 278 nm for the quantification (Chandra et al 2014a).…”
Section: Quantification Of Phenolic Compounds By Hplcmentioning
confidence: 99%